2015
DOI: 10.1111/cup.12636
|View full text |Cite
|
Sign up to set email alerts
|

Langerhans cell histiocytosis and Erdheim‐Chester disease, both with cutaneous presentations, and papillary thyroid carcinoma all harboring the BRAFV600E mutation

Abstract: Langerhans cell histocytosis (LCH) and Erdheim-Chester disease are two rare histiocytic disorders. Their occurrence in the same patient is more infrequent, but has been described. We report a case of a 38-year-old woman who presented with a diagnosis of single system cutaneous LCH. Subsequently, she developed multiple papules on her extremities consistent with a non-LCH xanthogranuloma type lesion. BRAF(V600E) mutation immunostain, VE1 was positive in the skin lesion, which was confirmed by molecular polymeras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 17 publications
1
23
0
Order By: Relevance
“…One patient had chronic myelomonocytic leukaemia and one had myelodysplastic syndrome, which further supports the hypothesis that a clonal abnormality on a common bone marrow precursor may be shared by LCH and myeloid disorders (33). Recently, Johnson et al (34) reported a patient with a BRAF V600E mutation in ECD skin lesions and a BRAF V600E mutation in a concomitant papillary thyroid carcinoma. The proportion of associated malignancies in our study (32%) was similar to those in a previous series of skin limited LCH (28%) (8), although higher than described previously in larger series of adult patients with LCH (6.2% in (10)).…”
Section: Discussionsupporting
confidence: 61%
“…One patient had chronic myelomonocytic leukaemia and one had myelodysplastic syndrome, which further supports the hypothesis that a clonal abnormality on a common bone marrow precursor may be shared by LCH and myeloid disorders (33). Recently, Johnson et al (34) reported a patient with a BRAF V600E mutation in ECD skin lesions and a BRAF V600E mutation in a concomitant papillary thyroid carcinoma. The proportion of associated malignancies in our study (32%) was similar to those in a previous series of skin limited LCH (28%) (8), although higher than described previously in larger series of adult patients with LCH (6.2% in (10)).…”
Section: Discussionsupporting
confidence: 61%
“…BRAF mutations are involved in tumour progression and metastasis in thyroid carcinoma,18 in colon carcinoma,19 in glioma20 and melanoma 21. It has also been reported in rare benign tumours such as metanephric adenoma of the kidney 22…”
Section: Discussionmentioning
confidence: 99%
“…The mixed histiocytoses represent disorders in which components of different histiocytoses occur in concert. This not an ununsual observation; and even BRAF mutations may be found in both components, indicating a common origin of the diseases [102,223]. Biology and treatment depend on the individual components found in the tumor, which are discussed in the specific sections.…”
Section: Mixed Ecd and Lchmentioning
confidence: 99%